Self-organized spatial patterns of carbonate formed via a nonclassical crystallization pathway. Issue 45 (1st November 2016) - Su, Yiping; Cui, Mingfang; Zhu, Jianhua; Li, Yali; Yan, Jufen
Abstract : Remarkable three dimensionally coaxial motifs with analogous pleated and terraced stereoscopic bands have been presented herein via a cationic polyelectrolyte-induced liquid precursor process with synergistic strontium ions. This may provide a fascinating model to understand the growth of crystalline surface topographic structures. Abstract : Self-organized spatial motifs of calcium carbonate with banded or concentric ring patterns are presented here through a cationic polyelectrolyte-induced nonclassical crystallization process in combination with synergistic strontium ions.